PENGARUH INOVASI PRODUK DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING: Studi UMKM Sektor Kuliner di Kecamatan Nganjuk - Ryza Wahyu Anofa; Adi Santoso; Fery Setiawan (Gapenas Publisher, 2022)
This study aims to test the influence of product innovation and entrepreneurial orientation on marketing performance with competitiveness as an intervening variable in MSMEs engaged in the culinary business sector in Nganjuk Regency. MSMEs that hold urgency in the economic development scheme in Indonesia must make product innovation and entrepreneurial orientation as part of their marketing management. The method used in this study is through a quantitative approach with data collection through observation, documentation, literature, and questionnaires. This research uses data analysis, namely through instrument tests and path test analysis to answer related to the hypothesis proposed. Instrument tests are used as a model in measuring the validity and validity of a statement through validity tests and reliability tests. Meanwhile, path analysis is used to determine the influence between variables through regression, determination, t test, and sobel test. The results obtained from this study are that there is an influence between product innovation and entrepreneurial orientation on marketing performance with competitive advantages as an intervening variable